United Kingdom : Financial Sector Assessment Program-Supervision and Systemic Risk Management of Financial Market Infrastructures-Technical Note. (IMF Staff Country Reports; Country Report ;, 2016)
The main objective of this technical note is to analyze the supervision and systemic risk management of financial market infrastructures (FMIs) in the United Kingdom. It focuses on the supervision of FMIs, including the regulatory framework, supervisory practices, available resources, transparency, adoption of international standards and coordination and cooperation mechanisms among authorities, both domestically and cross-border; identification and management of interdependencies among FMIs, clearing members and markets, as well as other mechanisms for monitoring of system-wide risks that may exacerbate a crisis and impact financial stability in the United Kingdom and worldwide; and recovery and resolution of FMIs as relatively new instruments to sustain critical operations and services.